P53 Promotes chemoresponsiveness by regulating hexokinase II gene transcription and metabolic reprogramming in epithelial ovarian cancer. Issue 11 (4th September 2019) - Han, Chae Young; Patten, David A.; Lee, Seung Gee; Parks, Robin J.; Chan, David W.; Harper, Mary‐Ellen; Tsang, Benjamin K.
Abstract: Metabolic reprogramming (including the Warburg effect) is a hallmark of cancer, yet the association between the altered metabolism and chemoresistance remains elusive. Hexokinase II (HKII) is a key metabolic enzyme and is upregulated in multiple cancers. In this study, we examined the impact of targeting metabolism via silencing of HKII on chemoresistance in ovarian cancer (OVCA). In addition, the regulatory molecular mechanism of tumor metabolism was examined using gain‐ and loss‐of‐function approaches in epithelial OVCA cell lines of various histological subtypes. We demonstrated that cisplatin (CDDP)‐induced p53‐mediated HKII downregulation is a determinant of chemosensitivity in OVCA. Silencing of HKII sensitized chemoresistant OVCA cells to apoptosis in a p53‐dependent manner. As a negative regulator, p53 suppressed HKII transcription by promoter binding and decreased glycolysis. Pyruvate dehydrogenase kinase‐1 (PDK1) is a key regulator of cell proliferation involved in Akt signaling axis. Our Gene Expression Profiling Interactive Analysis (GEPIA) and molecular studies also revealed that PDK1, an upstream activator strongly correlates with HKII expression and regulates its metabolic activity. Finally, we demonstrated that the clinically approved drug metformin sensitizes chemoresistant OVCA cells to CDDP via PDK1‐HKII pathway. Collectively, our data implicate that p53‐‐PDK1‐HKII axis is a central regulatory component of metabolism conferring chemoresistance in OVCA.